The Future as a Construction Project of the Social World - Mikayelyan, Meri (Bulletin of Yerevan University E: Philosophy, Psychology, 2015)
It is very difficult to imagine an era, the representatives of which wouldn’t think about their future through filling the gaps of present with projects of future. In the article, the utopia is submitted as a project of future construction, which is the embodiment of expectations, the aspiration to vital transformations and the statement of alternatives. Utopian projects are results of social imagination, which appeal social aspirations and dangers to life as a demonstration of the possible. The image of the desired future of that society depends on the degree of development, valuable system and moral guidelines. In the modern world, parallel with an acceleration of a vital rhythm, the utopian projects mostly belong to a short-term outlook. They attempt to provide for a person certain reference points in the unstable social world.